ANALISIS PEMANFAATAN APLIKASI MARBEL SEBAGAI MEDIA LITERASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Gesika Avelina; Rendy .S. Sambara; Allya Fadhillah Kurniawaty Hasan; Difya Nurpratiwi Moha; Riska Ali (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to analyze the utilization of the Marbel application as a literacy learning medium in Islamic Religious Education (IRE) at the elementary school level. The study employed a qualitative descriptive approach using a library research method. Data were collected from scientific journals, books, official Marbel documentation, and relevant previous studies, and analyzed using content analysis. The findings reveal that Marbel provides seven main features, namely alphabet recognition, vowels, consonants, syllables, educational games, word arrangement, and word guessing. These features integrate visual, audio, animation, and gamification elements that effectively support students' early literacy development. In Islamic Religious Education, literacy skills serve as an essential foundation for understanding religious learning materials. Therefore, the Marbel application has the potential to serve as an interactive, innovative, and appropriate supporting learning medium for Islamic Religious Education in the digital era.